COST OF CARE FOR VETERANS RECEIVING PRIMARY CARE IN PATIENT ALIGNED CARE TEAMS (PACT) VS. GERIATRIC PACTS. (11th November 2018) - Phibbs, C; Kinosian, B; Hong, J; Scott, W; Edes, T; Allman, R; Shay, K; Intrator, O
Abstract: GeriPACTs are geriatric-focused primary care teams with lower caseloads (2/3 of regular primary care (PACT)) and additional team members (e.g., pharmacy) to address the complex needs of patients with potentially higher need for geriatric and extended care services. We examined the effect of GeriPACT on total VA healthcare expenditures. Veterans in PACT or GeriPACT in FY2014 at 84 VA Medical Centers or Community Based Outpatient Clinics with verified GeriPACT;. JEN Frailty Index, a measure assessing the need for long-term institutionalization. NOSOS, VA's refinement of the Medicare HCC model, was used to create expected expenditures. Regressions estimated the effect of GeriPACT on log expenditures comparing GeriPACT Veterans to propensity score weighted Veterans receiving regular care (PACT). The final sample was 239, 430 (26, 296 in GeriPACT). The propensity-weighted estimates show that Veterans managed by GeriPACT had costs that were 7% (P<0.01) lower than those for patients managed in PACT.